The teacher's role in the interaction between software and mathematics education theories and its effect on the creativity of Sampad students - Seyed Mostafa Hamidi; Ali Zaeembashi; Mehrdad Namdari; Ashraf Karamzadeh (ریاضی و جامعه)
Mathematical Challenge is one of the main components in mathematics education, which aims to improve the ability of learners in the field of mathematics. Also, creativity is a personal and social characteristic that leads to the development of people at all levels and in all historical periods. In fact, applying information and knowledge and using creativity in solving problems is very important. In between, for a mathematics teacher, in addition to having good techniques and knowledge, the use of software and theories of mathematics education is also effective on the flourishing of students' talent and creativity and helps them to solve a higher-level problem. In geometric concepts, using Euclid's principles and mastering them gives the teacher a better perspective for the problem solving process. In this article, a geometrical problem suitable for the 8th and 9th grade level has been proposed for the 7th grade in Sampad school, and while expressing the importance of Euclid's principles, both the dynamic environment of mathematics and the paper-pencil environment have been used. By using the Van Hiele’s Theory in mathematical education, by designing an educational scaffold and dialogue between the teacher and students and with the help of Variation Theory, the answer of the problem was guessed by several students and a creative student gave a complete answer. Finally, we stated the problem as if and only if. In the meantime, Dimensional Deconstruction of Shapes was also used in the dynamic environment and paper-pencil environment.